Investigation of Stilbenoids as Potential Therapeutic Agents for Rotavirus Gastroenteritis - Judith M. Ball; Fabricio Medina-Bolivar; Katelyn Defrates; Emily Hambleton; Megan E. Hurlburt; Lingling Fang; Tianhong Yang; Luis Nopo-Olazabal; Richard L. Atwill; Pooja Ghai; Rebecca D. Parr (Advances in Virology)
Rotavirus (RV) infections cause severe diarrhea in infants and young children worldwide. Vaccines are available but cost prohibitive for many countries and only reduce severe symptoms. Vaccinated infants continue to shed infectious particles, and studies show decreased efficacy of the RV vaccines in tropical and subtropical countries where they are needed most. Continuing surveillance for new RV strains, assessment of vaccine efficacy, and development of cost effective antiviral drugs remain an important aspect of RV studies. This study was to determine the efficacy of antioxidant and anti-inflammatory stilbenoids to inhibit RV replication. Peanut (A. hypogaea) hairy root cultures were induced to produce stilbenoids, which were purified by high performance countercurrent chromatography (HPCCC) and analyzed by HPLC. HT29.f8 cells were infected with RV in the presence stilbenoids. Cell viability counts showed no cytotoxic effects on HT29.f8 cells. Viral infectivity titers were calculated and comparatively assessed to determine the effects of stilbenoid treatments. Two stilbenoids, trans-arachidin-1 and trans-arachidin-3, show a significant decrease in RV infectivity titers. Western blot analyses performed on the infected cell lysates complemented the infectivity titrations and indicated a significant decrease in viral replication. These studies show the therapeutic potential of the stilbenoids against RV replication.